A multiwavelength study of star formation in 15 local star-forming galaxies. Issue 3 (27th May 2021) - Smith, Madison V; van Zee, L; Salim, S; Dale, D; Staudaher, S; Wrock, T; Maben, A
ABSTRACT: We have fit the far-ultraviolet to mid-infrared spectral energy distributions (SEDs) for several nearby galaxies (<20 Mpc). Global, radial, and local photometric measurements are explored to better understand how SED-derived star formation histories (SFHs) and classic star formation rate tracers manifest at different scales. Surface brightness profiles and radial SED fitting provide insight into stellar population gradients in stellar discs and haloes. A double exponential SFH model is used in the SED fitting to better understand the distributions of young versus old populations throughout these galaxies. Different regions of a galaxy often have undergone very different SFHs, either in strength, rate, timing, or some combination of all these factors. An analysis of individual stellar complexes within these galaxies shows a relationship between the ages of stellar clusters and how these clusters are distributed throughout the galaxy. These star formation properties are presented alongside previously published H i observations to provide a holistic picture of a small sample of nearby star-forming galaxies. The results presented here show that there is a wide variety of star formation gradients and average stellar age distributions that can manifest in a ΛCDM universe.